2010
DOI: 10.1007/s12149-010-0359-9
|View full text |Cite
|
Sign up to set email alerts
|

Normoglycemic plasma glucose levels affect F-18 FDG uptake in the brain

Abstract: Our results indicated that plasma glucose levels that are within the normoglycemic range have a small but systematic effect on F-18 FDG uptake in the brain (following an inverse relationship). Normalizing plasma glucose levels to a standard glucose concentration successfully reduced the intra-subject variability of SUV measures. Inter-subject variability, however, remained high suggesting that other factors have an influence as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
3
19
1
1
Order By: Relevance
“…Similar to prior reports, we found that cerebral cortical FDG uptake has a negative inverse relationship to plasma blood glucose levels; with decreasing brain SUV as blood glucose levels increase [4,5]. Our inclusion of oncology patients rather than normal subjects allowed us to consider plasma blood glucose levels as a continual variable resulting in linear regression modeling rather than categorical comparisons.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to prior reports, we found that cerebral cortical FDG uptake has a negative inverse relationship to plasma blood glucose levels; with decreasing brain SUV as blood glucose levels increase [4,5]. Our inclusion of oncology patients rather than normal subjects allowed us to consider plasma blood glucose levels as a continual variable resulting in linear regression modeling rather than categorical comparisons.…”
Section: Discussionsupporting
confidence: 74%
“…Quantitative parametric imaging techniques have further improved brain PET diagnostic accuracy, interobserver agreement and reader training [2,3]. Hyperglycemia is known to influence brain FDG uptake [4,5], and consensus imaging protocols advise brain FDG PET/CT after a 4 h fast to achieve desirable blood glucose levels in the range of <160 mg/dL, as a threshold for hyperglycemia [68]. However, two recent studies report concern that milder degrees of hyperglycemia could potentially confound brain FDG PET/CT imaging by producing patterns of decreased cortical brain FDG uptake that could potentially mimic patterns seen in Alzheimer disease, using quantitative voxel-based parametric techniques [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…and compatible glucose uptake in the brain. Similar to prior studies, cerebral cortical FDG uptake had a negative relationship with blood glucose levels in this study (12,13).…”
Section: Resultssupporting
confidence: 90%
“…Emission sinograms were normalized and corrected for attenuation and decay of radioactivity and iteratively reconstructed using OSEM2D (4 iterations and 16 subsets). 31 PET data were not corrected for blood glucose levels, because previous reports indicate that glucose correction does not improve the inter-subject variability 32 and it may even introduce more noise. 33 A 10-minutes frame of the [ 18 F]FDG PET scan, starting 50 minutes post injection, was used to explore the differences in brain glucose metabolism between the groups.…”
Section: Pet Image Reconstruction and Analysismentioning
confidence: 99%